Social media as a democratic space: Language, irony and post-truth - Mariscal Vega, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research is a study on the relationship between social media and the transformation of language. It is based on the hypothesis that postmodern society is a relational network directly modified by the digital phenomenon. Thus, life in the network generates a metalanguage by virtue of which the “real world” originates. Through a review of the scientific literature and a theoretical approach based on surveys of young users of social networks, a hermeneutic analysis of key elements of our time and as controversial as the use of irony or post-truth is presented.